FINANCIAL LIBERALIZATION AND ECONOMIC GROWTH IN INDONESIA - Astuti, Rini D (Jurnal Ekonomi & Studi Pembangunan, 2005)
The objective of this study was to examine the empirical relationship between financial and economic growth by using broad money as a percentage of GDP and bank credit to the private sector as a percentage of GDP as an indicators of financial liberalization. It argues that broad money as a percentage of GDP have a clear disadvantage over economic growth in Indonesia during 1970-2002. The main findings are as follows: First, in short run, the study finds its measure of broad money as a percentage of GDP to have a significantly negative effect on the economic growth, and it measure of bank credit to the private sector as a percentage of GDP has no significantly positive effect on the economic growth. Second, in long run, it finds the impact of broad money as a percentage of GDP and bank credit to the private sector as a percentage of GDP on economic growth to be consistent with the short-run.